A companion to Marx's Capital. Volume two - Harvey, David, 1935- (London : Verso, 2013)
"The biggest financial crisis since the Great Depression shows no si gn of coming to a close and Marx's work remains key in understanding th e cycles that lead to recession. For nearly forty years, David Harvey h as written and lectured on Capital, becoming one of the world's most fo remost Marx scholars.Based on his recent lectures, and following the su ccess of his companion to the first volume of Capital, Harvey turns his attention to Volume 2, aiming to bring his depth of learning to a broa der audience, guiding first-time readers through a fascinating and hith erto neglected text. Whereas Volume 1 focuses on production, Volume 2 l ooks at how the circuits of capital, the buying and selling of goods, r ealize value.This is a must-read for everyone concerned to acquire a fu ller understanding of Marx's political economy"--
"The biggest financial crisis since the Great Depression shows no si gn of coming to a close, and Marx's work remains key in understanding t he cycles that lead to recession. For nearly forty years, David Harvey has written and lectured on Capital, becoming one of the world's foremo st Marx scholars. Based on his recent lectures, and following the succe ss of his companion to the first volume of Capital, Harvey turns his at tention to Volume 2, aiming to bring his depth of learning to a broader audience, guiding first time readers through a fascinating and hithert o neglected text. Whereas Volume 1 focuses on production, Volume 2 look s at how the circuits of capital, the buying and selling of goods, real ize value. This is a must-read for everyone concerned to acquire a full er understanding of Marx's political economy"--
Includes bibliographical references and index.
Keywords: Marx, Karl, -- 1818-1883.